The effects of plant secondary metabolites from coniferous needle leaf litter on the leaf litter decomposition of Betula albo-sinensis burk - Zhang, Xiaoxi; Liu, Hui; Zhou, Wenxing; Li, Jiajia; Lei, Hangyu; Ji, Yongkang; Wang, Boya; Liu, Zengwen (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this study, leaf litters of Betula albo-sinensis and 5 coniferous species were used as samples. The B. albo-sinensis leaf litter was buried in soil and termly treated with the water extracts of five types of coniferous leaf litter for a 6-month simulation decomposition experiment. The dynamics of mass loss and nutrients (C, N, P, and K) content of leaf litter and the soil enzymatic activities were measured to investigate the effects of plant secondary metabolites (PSM) from coniferous leaf litters on the decomposition processes of B. albo-sinensis leaf litter. The results indicated that the extracts of Pinus tabuliformis, Platycladus orientalis, P. armandii and Larix principis-rupprechtii leaf litters significantly inhibited the whole decomposition process and overall nutrients release of B. albo-sinensis leaf litter, while the extracts of Picea asperata leaf litter exhibited no significant influence. The general suppression of PSM on the soil sucrase, carboxymethyl cellulase and β-glucosidase activities might be the main reason leading to the inhibitory effects of the extracts of P. tabuliformis, P. orientalis, P. armandii and L. principis-rupprechtii leaf litter. The species causing inhibitory effects, especially L. principis-rupprechtii, was not recommended to be planted mixed with B. albo-sinensis, or their planting density should be lower in the mixed forests.